Properties of Lagrangian distributions. Issue 3 (1st February 2016) - Imoto, Tomoaki
Abstract: Lagrange's expansion is the power series expansion of the inverse function of an analytic function, and it leads to general Lagrangian distributions of the first kind as well as of the second kind. We present some theorems in which different sets of two analytic functions provide a Lagrangian distribution. Potential applicability of the theorem to tandem queueing process is studied.